Algorithm for Detecting Acoustic Traces of Neutrino Decay - Belyakov, Askold (Journal La Multiapp, 2024)
In the articles "Doppler Effect and Acoustic Trails of Neutrinos" and "Neutrinos above the Earth's surface", published in the journal "LA MULTIAPP" on February 25, 2022 and July 12, 2023, I was forced to touch on the astrophysical topic when, in the flow of data obtained in the process Monitoring acoustic noise with a recorder with a Nyquist frequency of 5 kHz, at a depth of 1000 m in the earth's crust, events began to be frequently observed, the shapes and frequencies of which are not typical for seismology and geophysics, and had not previously been observed by anyone. The shape of some events was very similar to the traces of neutrino decay, such as the bipolar pulse and the “diamond”, recorded by acoustic detectors in seawater. Subsequently, when recording high-frequency acoustic processes on the Earth's surface with a recorder with a Nyquist frequency of 50 kHz, events were discovered that were even more similar to traces of neutrino decay. At the same time, a “strange” association of some events of unknown origin with the field extrema of the power electrical network of a large city was discovered. To avoid erroneous conclusions, it is necessary to understand the origin of this “strangeness”.